2011
DOI: 10.1007/s10886-011-9953-0
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and Electroantennogram Responses of Male Mediterranean Fruit Fly to Volatile Chemicals from Persea, Litchi and Ficus Wood

Abstract: Trimedlure is the most effective male-targeted lure for the Mediterranean fruit fly, Ceratitis capitata (Wiedemann). A similar response is elicited by plant substances that contain α-copaene, a naturally-occurring sesquiterpene. α-Copaene is a complex, highly-volatile, widely-distributed plant compound, and male C. capitata respond to material from both hosts (e.g., Litchi chinensis) and non-hosts (e.g., Ficus benjamina) that contain α-copaene. Avocado, Persea americana, recently was found to contain varying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 59 publications
0
36
0
1
Order By: Relevance
“…ax/(b ϩ x), where x represents the substrate dose in milliliters of saturated vapor, y represents the normalized EAG response, and the coefÞcients a and b represent maximum EAG response and receptor binding afÞnity, respectively. Hyperbolic equations commonly are used for ligand-binding studies, and have been shown previously to serve well for characterization of EAG doseÐresponse relationships in insects (Kendra et al 2008(Kendra et al , 2009Niogret et al 2011b;Jenkins et al 2012). The EAG regression equations were as follows: manuka oil lure: y ϭ 77.42x/(0.74 ϩ x), R 2 ϭ 0.986; phoebe oil lure: y ϭ 106.15x/(0.96 ϩ x), R 2 ϭ 0.979; and silkbay wood volatiles: y ϭ 105.93x/(0.61 ϩ x), R 2 ϭ 0.982.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ax/(b ϩ x), where x represents the substrate dose in milliliters of saturated vapor, y represents the normalized EAG response, and the coefÞcients a and b represent maximum EAG response and receptor binding afÞnity, respectively. Hyperbolic equations commonly are used for ligand-binding studies, and have been shown previously to serve well for characterization of EAG doseÐresponse relationships in insects (Kendra et al 2008(Kendra et al , 2009Niogret et al 2011b;Jenkins et al 2012). The EAG regression equations were as follows: manuka oil lure: y ϭ 77.42x/(0.74 ϩ x), R 2 ϭ 0.986; phoebe oil lure: y ϭ 106.15x/(0.96 ϩ x), R 2 ϭ 0.979; and silkbay wood volatiles: y ϭ 105.93x/(0.61 ϩ x), R 2 ϭ 0.982.…”
Section: Resultsmentioning
confidence: 99%
“…IdentiÞcation of ethanol as a standard reference compound for Xyleborus species permitted normalization of EAG responses and comparative analyses of olfaction, as has been done with other pest insects (Kendra et al 2008(Kendra et al , 2009Niogret et al 2011b;Jenkins et al 2012). Aside from the difÞculties with dissection and manipulation of such small antennae, the main drawback was that the excised antennae were viable for only Ϸ30 min, necessitating short EAG recording sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male C. capitata respond to material from both hosts (e.g., Litchi chinensis Sonn.) and non-hosts (e.g., Ficus benjamina L.) that contain α-copaene (Warthen and McInnis 1989;Niogret et al 2011). While α-copaene is reported to be 2-5 times more attractive than trimedlure, difficulties in obtaining this compound in quantities sufficient for large scale trap deployment have prevented its use as a field lure (Cunningham 1989).…”
Section: Genus Ceratitismentioning
confidence: 99%